Analisis Kenaikan Tarif Pajak Penambahan Nilai (Ppn) 12% Pada Minat Beli Masyarakat Di Kota Banjarbaru - Iin Muyasarah; Nur Habibah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The increase in the Value Added Tax (VAT) rate to 12% has caused concern among the public, especially the lower-middle-class population in Banjarbaru city. The increase in tax is seen as an additional economic burden for the people, as the tax was initially 11% and is now raised to 12%. Based on the public's concerns about the VAT increase, the government has provided information that the 12% VAT rate applies only to luxury goods and luxury services. With this regulation, it is hoped that the policy will be fair to all segments of society by imposing the new VAT rate only on luxury goods and services. This research uses a literatur review method, gathering data from published articles, news, and other supporting books. The results of this study show that the 12% VAT rate increase does not affect the public's purchasing interest, as the regulation applies only to luxury goods. However, a decrease in income has been observed in Banjarbaru city from 2022 to 2024. The 12% VAT policy, which began implementation in early 2025, based on updated economic growth data, has caused a decline of 10%. Inflation has not experienced a significant impact from the increase in VAT because of the regulation related to the 12% VAT rate.